The rhythm of modernization: how values change over time - Tormos, Raül (International studies in sociology and social anthropology, 2012)
"In this chapter I review the three main theories of values, the still limited literature on value change, and the contributions of socialization studies to understanding the dynamics of sociopolitical orientations. I devote special attention to Inglehart's general theory of modernization upon which I base my subsequent empirical analysis. I reflect on what values are and the main approaches to the study of values, those of Rokeach, Schwartz, and Inglehart"--